The Salary Rate Prediction in the Thailand IT Job Market - Amornwatee, Punika; Teerawanviwat, Duanpen; Siripanich, Pachitjanut (Journal of Applied Statistics and Information Technology, 2021)
The purpose of this study found the affected factor of prediction IT job salary and built the IT job salary rate prediction webpage. We use Multiple Linear Regression to create an IT job salary prediction model from survey data 2019 of the Thai Programmer Association. We selected the highest r-squared model by the All Possible Regression solution and apply in an IT job salary rate prediction webpage that get it easier to use. From the study, we found that some role job models are unable to predict certain accuracy. First, the data is not intended to predict salaries. Second, the sizes and ratios of the sample groups are too different and finally, the predicting salary rate has many other factors that will make an impact on it. In this research, there is not yet information on all factors that can cover the predicted of accurate salary rates by a hundred percent. Therefore, the models used for calculations on this webpage are only part of the decision-making process for finding a salary for an individual.